Liveable Communities: A Case Study of Availability, Proximity, and The Quality of Critical Infrastructure in Colombo, Srilanka - Tennakoon, Maheshi; Kulatunga, Udayangani (CSID Journal of Infrastructure Development, 2024)
The concept of livable communities has become increasingly significant in regional planning, aiming to improve the quality of life for residents. Despite continued investment in critical infrastructure in developing countries, the enhancement of livability has not kept pace with infrastructure development. This study investigates the impact of crucial infrastructure on community livability, utilizing a holistic single case study approach with Colombo as the case study. The relationship between critical infrastructure development and urban livability serves as the unit of analysis. Data were collected through semi-structured interviews with ten subject matter experts and analyzed using manual content analysis. The research finds that the availability of essential services—education, healthcare, transportation, energy, and communication—constitutes the foundation of a livable community. However, compared to its availability, inadequate attention to the quality and proximity of critical infrastructure is a fundamental reason for not achieving livability objectives in developing nations. The study identifies four aspects of proximity (residential, workplace, transportation, and emergency services) and seven aspects of quality (reliability, timeliness, safety and security, accessibility, efficiency, effectiveness, and customer satisfaction) as crucial for attaining livability standards. A key insight is the lack of consideration for community perceptions of critical infrastructure development in developing countries, hindering urban livability efforts. The study suggests Community-Driven Needs Assessment (CDNA), Participatory Budgeting, Community Infrastructure Committees, Crowdsourced Design Challenges, and Knowledge Sharing Platforms as strategies to enhance community involvement in planning critical infrastructure. It recommends further empirical research in similar contexts to evaluate the effectiveness of these approaches.